2020
DOI: 10.1016/j.asmr.2020.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Conversion of Hip Arthroscopy to Total Hip Arthroplasty: A Large Closed-Cohort Study

Abstract: Purpose To evaluate risk factors for conversion of hip arthroscopy to total hip arthroplasty (THA) within 2 years in a closed patient cohort. Methods This study was a case series of consecutive hip arthroscopy procedures from September 2008 to November 2018 in the electronic medical record of Kaiser Permanente Northern California. Patients were included with minimum 2-year follow-up or if they had conversion to THA within 2 years (the primary outcome) regardless of foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
0
12
1
Order By: Relevance
“…Kester et al 19 and West et al 36 identified patient age, female sex, and index procedure performed by a low-volume surgeon as risk factors for undergoing revision hip arthroscopy within 2 years. Although studies have associated these and other numerous risk factors with early conversion from hip arthroscopy to THA, 1 , 32 previous studies to our knowledge have not reported an association between depression and revision hip arthroscopy.…”
Section: Discussionmentioning
confidence: 85%
“…Kester et al 19 and West et al 36 identified patient age, female sex, and index procedure performed by a low-volume surgeon as risk factors for undergoing revision hip arthroscopy within 2 years. Although studies have associated these and other numerous risk factors with early conversion from hip arthroscopy to THA, 1 , 32 previous studies to our knowledge have not reported an association between depression and revision hip arthroscopy.…”
Section: Discussionmentioning
confidence: 85%
“…Hip arthroscopy in patients older than 40 years should be approached with extreme caution, as increasing age has been strongly associated with poorer outcomes and higher rates of failure. 2,16,19,23,49,50 However, recent evidence brings this age-associated paradigm into question. Two recent systematic reviews on hip arthroscopy in patients older than 40 years came to parallel conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The authors [ 4 ] from California, USA, evaluated the risk factors for conversion of hip arthroscopy to THA within 2 years in a closed patient cohort. This study was a case series of consecutive hip arthroscopy procedures from September 2008 to November 2018 in the electronic medical record of Kaiser Permanente Northern California.…”
Section: Risk Factors For Conversion Of Hip Arthroscopy To Tha: a Large Closed-cohort Studymentioning
confidence: 99%